2017
DOI: 10.1159/000479441
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Vascular Endothelial Growth Factors Protect Retinal Pigment Epithelium Cells Against Oxidation by Modulating Nitric Oxide Release and Autophagy

Abstract: Background/Aims: the anti-vascular endothelial growth factors (VEGF), Aflibercept and Ranibizumab, are used for the treatment of macular degeneration. Here we examined the involvement of nitric oxide (NO), mitochondria function and of apoptosis/autophagy in their antioxidant effects in human retinal pigment epithelium cells (RPE). Methods: RPE were exposed to Ranibizumab/Aflibercept in the absence or presence of NO synthase (NOS) inhibitor and of autophagy activator/blocker, rapamicyn/3-methyladenine. Specific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
47
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 3,606 publications
(50 citation statements)
references
References 130 publications
3
47
0
Order By: Relevance
“…Oxidative stress plays an important role in retinal angiogenesis [34,35]. HIF, the pivotal mediator of cellular responses to oxygen stress, was decreased by imatinib treatment [35]. This result suggests that imatinib might also suppress angiogenesis by ameliorating oxidative stress in retinas.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 95%
See 1 more Smart Citation
“…Oxidative stress plays an important role in retinal angiogenesis [34,35]. HIF, the pivotal mediator of cellular responses to oxygen stress, was decreased by imatinib treatment [35]. This result suggests that imatinib might also suppress angiogenesis by ameliorating oxidative stress in retinas.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 95%
“…In addition, we found imatinib could inhibit the phosphorylation of Erk1/2, which is involved in the survival, proliferation, and migration of vascular cells and is recognized as part of an important signaling pathway closely involved in angiogenesis [33], suggesting that the reduction of angiogenesis by imatinib may occur in part through inhibiting Erk1/2 signaling pathways. Oxidative stress plays an important role in retinal angiogenesis [34,35]. HIF, the pivotal mediator of cellular responses to oxygen stress, was decreased by imatinib treatment [35].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…GSH measurements were performed with a specific kit (Cayman Chemical), as previously performed (Grossini et al 2014;Surico et al 2015;De Cill a et al 2017).…”
Section: Gsh Assaymentioning
confidence: 99%
“…Since the expression of VEGF was intimately linked with the apoptosis state of RPE cells, which could be regulated by hyperoxidants, high glucose levels and cyclic stretch ( De Cillà et al, 2017 ; Oh et al, 2017 ; Wu et al, 2017 ), the beneficial effects of Kin against oxidative apoptosis were further analyzed. We found that Kin drastically reduced apoptosis of RPE cells compared with the H 2 O 2 -treated Vehicle group.…”
Section: Discussionmentioning
confidence: 99%